Alternative of Visual Based Learning (VBL) Method Based on Short Duration Video for The Instrumental Chemistry Subject in Chemistry Department - Riyanto Riyanto; Beta Wulan Febriana (Universitas Islam Indonesia, 2017)
ABSTRACT:There had been done a study of Visual Based Learning (VBL) method based on Short Duration Video for Instrumental Chemicals Subject in Chemistry Study Program of Mathematics and Natural Sciences Faculty (MNSF), Islamic University of Indonesia (Universitas Islam Indonesia—UII). VBL method is carried out by creating a short duration video about an instrument according to the syllabus of instrument 1 subject such as AAS, UV-Vis Spectrophotometer, FTIR, GC-MS, and CV. In order to determine the effect of VBL method using, an analysis of scores obtained between the experimental class and the control class is used. To determine the effect of VBL on psychomotor ability is done by observing directly when students do an experiment or practicum. The influence of VBL method application on student motivation was studied by using questionnaire. The results pointed out that the data of both samples (both classes) is homogeneous. T-test results: Two-Sample Assuming Equal Variances showed that there is a significant difference in the final scores mean between the experimental class and the control class. Based on the mean score it indicates that the VBL method is better while compared to the learning method without VBL. VBL method has a significant effect on students motivation andpsychomotor ability when it is viewed from observation of practicum and the score of practicum. The conclusion is that the VBL method is able to increase students' motivation and psychomotor ability in the Instrumental Chemistry subject.Keywords: Learning, video, chemistry, instrumentalReceived: 20 June 2017, Revised: 13 August 2017, Accepted: 1 September 2017